2021
DOI: 10.4018/978-1-7998-6825-5.ch020
|View full text |Cite
|
Sign up to set email alerts
|

Compulsory Citizenship Behavior and Perceived Stress Level in the Pandemic Process

Abstract: Turkey has been fighting against Coronavirus since March of 2020. During this period, healthcare workers who have been at high risk of becoming infected and transmitting the virus to their relatives were prohibited from resignation and going abroad. In the context of these prohibitions, this study aims to reveal how the stress levels and compulsory citizenship behaviors of healthcare workers were affected during the early stages of pandemic. According to the results of the study, middle-level stress, low-mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In addition to the potential stress caused by the characteristics of the job, intensification and precarious conditions cause nurses to suffer from high workloads and stress (Khademi et al, 2015;Youn et al, 2017;Hardiyono et al, 2020). During the COVID-19 pandemic, this workload has peaked, and the balance between work and family has been jeopardized Boztilki et al, 2021). In this process, it has become necessary to exhibit CCBs, such as working overtime without pay.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the potential stress caused by the characteristics of the job, intensification and precarious conditions cause nurses to suffer from high workloads and stress (Khademi et al, 2015;Youn et al, 2017;Hardiyono et al, 2020). During the COVID-19 pandemic, this workload has peaked, and the balance between work and family has been jeopardized Boztilki et al, 2021). In this process, it has become necessary to exhibit CCBs, such as working overtime without pay.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Extra-contractual work behaviors are imposed by organizations or management and are defined as compulsory citizenship behaviors (CCBs). Previous research indicates that nurses have found it increasingly hard to handle CCBs in extreme conditions such as the COVID-19 pandemic (Boztilki et al, 2021;Yildiz et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation